KCC2 inhibition and neuronal hyperexcitability promote extrinsic apoptosis dependent upon C1q - Ji, Jinglin; Choi, Catherine; Bope, Christopher E.; Dengler, Jacob S.; Moss, Stephen J.; Smalley, Joshua L. (Frontiers in Molecular Neuroscience, 2025)
IntroductionThe potassium chloride co-transporter 2 (KCC2) is the principal Cl− extrusion mechanism employed by mature neurons in the central nervous system (CNS) and plays a critical role in determining the efficacy of fast synaptic inhibition mediated by type A γ-aminobutyric acid receptors (GABAARs) to protect against epileptogenesis. It has previously been demonstrated that epileptic seizures down-regulate KCC2 and induce neuronal apoptosis through the extrinsic apoptotic pathway. However, the mechanism by which neuronal death is induced by KCC2 loss remains unknown. We have previously demonstrated that C1q copurifies with KCC2 in comparable amounts. C1q is responsible for synaptic elimination in the brain during development, aging and neurodegeneration.MethodsHere, we studied apoptotic induction in models of KCC2 loss of function and demonstrated the importance of C1q in this process using a constitutive C1qKO mouse model. We characterized the activation of different apoptotic pathways by measuring caspase 8 and caspase 9 cleavage as markers of extrinsic and intrinsic apoptosis, respectively.ResultsThis study demonstrates in vitro, ex vivo and following seizures in vivo, that reduced KCC2 function coincides with neuronal death by activating the extrinsic apoptotic pathway, which is contingent upon complement C1q. Moreover, kainic acid (KA)- and glutamate-induced excitotoxicity also selectively activates the extrinsic apoptotic pathway which is contingent upon C1q.DiscussionThese results strongly support the hypothesis that the KCC2/C1q protein complex plays a critical role in the apoptotic process that occurs following loss of KCC2 function.